Mine Detecting GPS-Based Unmanned Ground Vehicle - (:unkn) unknown (IEEE, 2009)
Mines which are located on the ground have been threating not only military forces but also civilians. These threating mines are classified as wooden, plastic and metal types. In this study a detector, which is able to detect all the mines placed on the ground, has been developed. Detecting and destroying the mines on a suspicious area without personel have been possible with remote control devices. In our work we aimed to produce a GPS-based mobile prototype vehicle carrying a system which can jam electromagnetic waves to blow up the mines with a remote control. This vehicle runs on solar energy and it can be steered by simulation glasses.
Keywords: mine; mine detector; unmanned ground vehicle (UGV); mobile robot